El corazón y la espada - Véjar, Carlos hijo; Ragona, Ubaldo; Wallace, Enrique; Romero, Cesar; Jurado, Katy; Iturbide, Rebeca (Flicker Alley, 2020)
"The Sword of Granada" (El corazón y la espada) is an old fashioned action-adventure about a trio of adventurers on a quest in Mexico. The group find themselves getting into mischief and have a lot of sword swashbuckling duels that test them and lead to their ultimate fates. Produced by Jorge García Besné (The Vengeance of the Vampire Women, Madame Death), "The Sword of Granada" (El corazón y la espada) is notable as the first 3D feature-film ever produced in Mexico. Presented for the first time on Blu-ray as a rarity in the outstanding "3-D Rarities: Volume II" collection from Flicker Alley (working with the 3-D Film Archive), the release is a little-seen adventure that is worth a look for genre fans. [www.blu-ray.com]